Prognostic Factors in Intestinal-Type Sinonasal Adenocarcinoma: A 10-Year Single-Center Retrospective Cohort Study - Afonso, Sara Pinto Costa; Silva, Ana Carolina Santos; Leal, Laurentino Manuel Mendes; Silva, Pedro Alberto Pinto da (Journal of Neurological Surgery Part B: Skull Base)
Objectives This study assesses the prognostic impact of tumor invasion patterns and anatomical topography in patients with primary intestinal-type sinonasal adenocarcinoma (ITAC). Specifically, we evaluate the relationship between key invasion sites and overall survival to improve risk stratification and surgical decision- making. Design and Setting A retrospective, single-center cohort study was conducted at Unidade Local de Saúde São João, Porto, Portugal. Participants Thirty patients with a primary diagnosis of sinonasal ITAC between 2014 and 2024 who underwent surgical resection were included. Main Outcome Measures Survival outcomes were evaluated using Kaplan-Meier survival analysis, with a specific focus on tumor laterality, dural and subpial invasion, sphenoid and orbital invasion, and overall tumor burden. Additionally, the effects of clinical and treatment-related parameters were evaluated. Results A significantly poorer survival was found in tumors with subpial invasion at diagnosis, (p < 0.001), whereas dural invasion showed a trend toward significance (p = 0.053). The influence of orbital and sphenoid invasion on survival was negligible. Left-seated tumors showed a worse prognosis compared to right-sided lesions (p = 0.003). Patients selected for purely endoscopic surgical approaches and gross total resection (GTR) were linked with better outcomes. Conclusion Our results emphasize the need for a comprehensive preoperative evaluation of important anatomical invasion locations and the prognostic importance of subpial invasion and tumor laterality in ITAC. Preoperatively identifying high-risk features may refine surgical planning and treatment choices, optimizing survival outcomes in this aggressive malignancy.